2018
DOI: 10.1111/jomf.12469
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence in Later‐Life Family Networks: Beyond Intergenerational Dyads

Abstract: In later life, changing conditions related to health, partnership, and economic status may trigger not only support but also conflict and ambivalence, with the consequent renegotiation of family ties. The aim of this study is to investigate both conflict and emotional support in the family networks of older adults, taking the research beyond the level of intergenerational dyads. We used a subsample of 563 elders (aged 65 years and older) from the Swiss Vivre/Leben/Vivere survey. Multiple correspondence analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
0
38
0
2
Order By: Relevance
“…Ambivalence coexists with emotional closeness, regular contact and support exchanges, and with conflict and discord (Connidis, ; Lüscher, ; van Gaalen & Dykstra, ; van Gaalen, Dykstra, & Komter, ; Willson, Shuey, Elder, & Wickrama, ). Ambivalence also spreads across family configurations when ambivalence among some family members affects others in the network (Girardin et al, ).…”
Section: An Interactive Multilevel Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambivalence coexists with emotional closeness, regular contact and support exchanges, and with conflict and discord (Connidis, ; Lüscher, ; van Gaalen & Dykstra, ; van Gaalen, Dykstra, & Komter, ; Willson, Shuey, Elder, & Wickrama, ). Ambivalence also spreads across family configurations when ambivalence among some family members affects others in the network (Girardin et al, ).…”
Section: An Interactive Multilevel Frameworkmentioning
confidence: 99%
“…Who will fill the gap left by the absence of a partner or children among growing numbers of older people who have very few or no kin in old age (Margolis & Verdery, )? Research on family configurations shows that those who are very old, poor, in poor health, widowed, and childless are at greater risk of being in family networks characterized by emotionally disengaged and unsupportive ties composed of a few friends or nobody at all (Girardin et al, ), reflecting the greater risks to particular groups of older people based on class and gender. With more unattached and childless older persons, an ever‐expanding circle of family and nonfamily ties becomes implicated in providing care.…”
Section: Making Our Research Count: Research and Applicationmentioning
confidence: 99%
“…Research also suggests that these background characteristics are likely to affect networks and personal relationships. For example, studies show that people with diminished resources and poor health have networks with lower levels of support and higher levels of difficulty (Girardin et al 2018). Variations in the volume of network support and difficulty by gender and race and ethnicity have also been observed (Nguyen 2017).…”
Section: -To 30-year-oldsmentioning
confidence: 99%
“…Ambivalence in these relationships appears to be fueled by a specific form of oscillation between dependency and autonomy among parents and grandparents, which results in tensions between involvement and interference (Connidis, 2015;Fingerman et al, 2004;Lüscher, 2002). Many studies have focused on grandparents' feelings of ambivalence (e.g., Girardin et al, 2018;Lüscher & Lettke, 2004;Neuberger & Haberkern, 2014;Pillemer & Suitor, 2002;Pillemer et al, 2007Pillemer et al, , 2012, while some have also included the parents' perspectives (e.g., Ferring et al, 2009;Fingerman et al, 2020;Gilligan et al, 2015a;Willson et al, 2003). These studies have shown that feelings of ambivalence are perceived as stressful and can have a negative impact on relationship quality, as well as detrimental consequences for the psychological well-being of both grandparents and adult children.…”
Section: Grandparental Involvement and Intergenerational Ambivalencementioning
confidence: 99%